Draft Eighth Five Year Plan 1990-95 Volume : I an Overview Government of Assam - Planning Commission (Planning Commission, 1990)
Assam is situated in the North-Eastern coroner of the country and forms the core of the North-Eastern Region comprising of besides Assam, Arunachal Pradesh, Manipur, Nagaland, Meghalaya, Mizoram and Tripura. It has common borders with all the six States of the Region, as also West Bengal, besides inter-national borders with Bangladesh and Bhutan and is linked with the rest of India by a narrow corridor through North Bengal.
Government of Assam, Planning and Development Department